Introduction to balanced nutrition in teaching for elementary school students - Erhan Dimas Nugraha; Asep Bayu Dani Nandiyanto (Jurnal Abmas, 2022)
The current condition in Indonesia, especially in children, is still experiencing a double burden of nutrition, namely lack of and excess nutrition. Many factors are involved in nutritional problems in Indonesia. One of the efforts that support the prevention of nutritional problems is through direct socialization to children by providing information about balanced nutrition so that it is expected to be able to educate from an early age, especially in choosing the types of food that are good for health and the introduction of body conditions related to nutritional disorders. The purpose of this study is that students in the Tugu Negeri Desa Cihideung, Parongpong District, West Bandung Regency, Indonesia get additional education about balanced nutrition and at the same time the introduction of canker sores as an example of a disease that can be caused by a nutritional disorder. filling out a questionnaire that is applied to early childhood with an age range of 7-9 years using pre-test and post-test questionnaires. The result is that from a total of 20 students who filled out the questionnaire, as many as 62 students (67%) experienced an increase in the score on their post test results, and as many as 100% of grade 1 students experienced an increase, this shows that the implementation can be well absorbed by most students. A good counseling process requires several supporting factors including careful preparation and during implementation, interactive material delivery techniques are needed, as well as good team coordination. Continuous activities need to be carried out to monitor the application of the knowledge gained from the results of the counseling so that it is hoped that there will be an increase in the health quality of Indonesian children. The child's body is stronger against infection with other diseases.   AbstrakKondisi saat ini di Indonesia khususnya pada anak-anak masih mengalami beban ganda gizi yaitu gizi kurang dan kelebihan gizi. Banyak faktor yang terlibat dalam masalah gizi di Indonesia. Salah satu upaya yang mendukung pencegahan masalah gizi adalah melalui sosialisasi langsung kepada anak-anak dengan memberikan informasi tentang gizi seimbang sehingga diharapkan dapat mengedukasi sejak dini terutama dalam memilih jenis makanan yang baik untuk kesehatan dan pengenalan kondisi tubuh yang berhubungan dengan gangguan gizi. Tujuan dari penelitian ini adalah siswa di Tugu Negeri Desa Cihideung, Kecamatan Parongpong, Kabupaten Bandung Barat, Indonesia mendapatkan edukasi tambahan tentang gizi seimbang sekaligus pengenalan penyakit sariawan sebagai contoh penyakit yang dapat diakibatkan oleh gangguan gizi. pengisian angket yang diterapkan pada anak usia dini dengan rentang usia 7-9 tahun menggunakan angket pre-test dan post-test. Hasilnya adalah dari total 20 siswa yang mengisi angket, sebanyak 62 siswa (67%) mengalami peningkatan nilai pada hasil post test-nya, dan sebanyak 100% siswa kelas 1 mengalami peningkatan. Hal ini menunjukkan bahwa pelaksanaannya dapat diserap dengan baik oleh sebagian besar siswa. Proses penyuluhan yang baik memerlukan beberapa faktor pendukung antara lain persiapan yang matang dan selama pelaksanaan diperlukan teknik penyampaian materi yang interaktif, serta koordinasi tim yang baik. Perlu dilakukan kegiatan yang berkesinambungan untuk memantau penerapan ilmu yang didapat dari hasil penyuluhan sehingga diharapkan terjadi peningkatan kualitas kesehatan anak Indonesia. Tubuh anak lebih kuat melawan infeksi penyakit lain. Kata Kunci: pengantar; gizi seimbang; bahan ajar; siswa sekolah dasar.